Aquarelle : Aqua real - Aqua reell - Aquarell - A.R. Penck. (Kassel : Kasseler Kunstverein, 1984)
Baselitz ; Beuys ; Buthe ; Disler ; Dokoupil ; Dorazio ; Droese ; Girke ; Graubner ; Keining ; Kirkeby ; Lassnig ; LeWitt ; Lüpertz ; Middendorf ; Paeffgen ; Paladino ; Penck ; Pichler ; Polke ; Prangenberg ; Raetz ; Reuter ; Richter ; Runge ; Schultze ; Tuttle ; Uecker ; Voss ; Wörsel
Aquarelle, Kasseler Kunstverein, Kassel, 16.11.1984 - 6.1.1985
boek